Determinants of ecosystem stability in a diverse temperate forest. Issue 11 (4th August 2020) - Dolezal, Jiri; Fibich, Pavel; Altman, Jan; Leps, Jan; Uemura, Shigeru; Takahashi, Koichi; Hara, Toshihiko
Abstract : Understanding how diversity affects ecosystem stability is crucial for predicting the consequences of continued habitat and biodiversity loss on ecosystem functions and services. Long‐term productivity stability in plant communities is often associated with greater species, phylogenetic or functional diversity, more complex size and age structures, or higher asynchrony in species fluctuations (compensatory dynamics), all potentially increasing community resistance to perturbations. However, the relative importance of these stabilizing pathways is still poorly understood, especially in old‐growth species‐rich forests. Here we explore how compensatory dynamics and multiple facets of diversity underpin temporal stability of wood biomass production over forty years in a Japanese temperate forest, based on more than 45 500 stem increments from 15 species. Whereas the effect of species richness and phylogenetic diversity was small, the old‐growth structural attributes markedly increased community stability via increased asynchrony in the performance of co‐occurring species. Greater standing tree volume, stem density and interspecific variation in growth rates enhanced productivity stability both directly and indirectly via increased asynchrony. This corroborates the predictions of increased compensatory dynamics with increased asymmetric competition for light in a more productive environment. Asymmetric competition in old‐growth patches, between dominant oaks and sub‐canopy shade‐tolerant firs and maples, is a major driver of productivity stability over time via compensatory dynamics. Overall productivity remains relatively constant in old‐growth patches, as abundant firs and maples in the lower canopy layers compensate for biomass losses in canopy oaks caused by aging, wind and snow disturbances. Younger forest patches, composed of fast‐growing, shade‐intolerant species, had a lower stability of productivity, with reduced stem basal area and tree density due to higher understory bamboo coverage preventing tree regeneration and growth. We provide new insights into mechanisms underlying the stability of ecosystem functioning in diverse forest ecosystems, and emphasize the importance of preserving and supporting old‐growth forests and their structural complexity.